Oral Health Status Among Pregnant Women Attending Gynae OPD of Tertiary Care Hospital in Rawalpindi - Samina Anjum, Naila Azam, Fatima Ali Raza Mughal, Sadia Huma, Wajeeha Jabeen , (Journal of Rawalpindi Medical College, 2021)
Objective: The objectives of this study were to determine the oral health status and treatment needs using DMFT & CPITN indices in pregnant women attending Gynae OPD of tertiary care Hospital in Rawalpindi, to Determine Association of Oral health status using DMFT and CPITN with socioeconomic status and to determine oral health status of various trimesters of pregnancy Materials and methods: An analytical cross-sectional study was carried out to assess the oral health status and treatment needs among pregnant women at Tertiary Care Hospital, Rawalpindi from April’ 2020 to September’ 2020. Consecutive sampling was used to select the study participants. An adaptive version of WHO questionnaire was used. Results were presented in the form of frequency tables. Chi square test of statistics was applied to assess the association between categorical DMFT and CPITN with the sociodemographic characteristics of the participating females. Results: The mean DMFT score pregnant females was 2.41 + 2.30 and were belonged to a middle socioeconomic status 43.8% (n=173). About 61.8% (n=244) of participants had DMFT total score 1-7. Whereas, majority of the participants were reported bleeding gums on probing 30.6% (n=121) on assessment by CPITN. The participating pregnant females also depicted the worsening of periodontal tissues (P=0.00) and dentition status (P=0.02). Socioeconomic status was not significantly associated with dentition (P=0.39) and periodontal status (P=0.69). Conclusion: The study revealed that oral health status was deteriorated during pregnancy. Education and gestational period were strong indicator for oral health status among pregnant women. Bleeding gums were reported in majority of participants during second trimester of pregnancy. Socioeconomic status was not significantly associated with oral health status by CPITN and DMFT score.